2011
DOI: 10.1007/s00262-011-1106-3
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic cyclophosphamide treatment in metastasized breast cancer patients: immunological effects and clinical outcome

Abstract: Severe immune suppression is frequent in late-stage tumor patients and promotes tumor immune evasion and subsequent tumor progression. Regulatory T cells (Treg) are major suppressors of anti-tumor immune responses. Therefore, targeting of Treg has become a key goal of anti-tumor therapy. Several preclinical and clinical observations suggest that Treg can be depleted by cyclophosphamide. Over a period of 3 months, we investigated the effect of metronomic low-dose cyclophosphamide on Treg numbers, suppressive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 32 publications
4
139
0
2
Order By: Relevance
“…41,77 A prolonged and more effective Treg inhibition was achieved by metronomic CTX regimens in patients with advanced solid tumors 6 or with metastatic breast cancer. 78 Moreover, metronomic temozolomide, an analog of dacarbazine, reduced the number and the suppressive function of circulating Tregs in rats bearing glioma, although it did not restrain tumor growth. 79 The role of CTX on MDSCs is more controversial.…”
Section: Effects On Regulatory Subsets and Pathwaysmentioning
confidence: 99%
“…41,77 A prolonged and more effective Treg inhibition was achieved by metronomic CTX regimens in patients with advanced solid tumors 6 or with metastatic breast cancer. 78 Moreover, metronomic temozolomide, an analog of dacarbazine, reduced the number and the suppressive function of circulating Tregs in rats bearing glioma, although it did not restrain tumor growth. 79 The role of CTX on MDSCs is more controversial.…”
Section: Effects On Regulatory Subsets and Pathwaysmentioning
confidence: 99%
“…Administration of high-dose cyclophosphamide severely affects all T cells. However, when used at low doses over a long term, the drug has been shown to selectively reduce highly proliferating Treg cells including those in the tumor tissues, and enhance anti-tumor immune responses in humans and rodents [73][74][75][76]. Furthermore, an increasing number of studies have shown the potentials and efficacy of low-dose metronomic cyclophosphamide in combination with other immunotherapeutic agents [77,78].…”
Section: Small Molecules For Treg Depletion or Functional Modulationmentioning
confidence: 99%
“…The previously mentioned clinical studies by Ghiringhelli, et al . 30 and Ge, at al ., 37 also described an increase in effector T cells upon mCTX treatment. In animal models skewing towards a Th1 profile with increased type I interferons and IL-2 upon mCTX treatment was observed, 40,41 which could correspond to the increase in IFNγ+ CD4 and CD8 T cells observed in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Conflicting results have been published about the effect of mCTX on the suppressive capacity of Tregs; in metastasized breast cancer patients 50 mg cyclophosphamide daily for three months resulted in an initial Treg reduction but a preservation of their suppressive function. 37 Another study in end stage cancer patients treated with 50 mg cyclophosphamide twice daily, one week on and one week off for one month, also found a selective reduction of Tregs, but also a suppression of their inhibitory functions. 30 Since we observed a downregulation of CTLA4 in aTregs, but an upregulation in nTregs, these inconsistent results could be explained by a subset dependent effect of mCTX.…”
Section: Discussionmentioning
confidence: 95%